Teachers' Perceptions of the Importance of 21st Century Skills (Critical Thinking, Communication, Collaboration, and Creativity) in the English Language Learning Process - Alya Zalsabila; Munir; Fitriyani (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
21st century skills are a set of abilities and competencies that are considered important for individuals to have in order to live, learn, and work successfully in today's fast-paced, complex, and technology-based globalization era. This study aims to explore English teachers' perceptions of the importance of 21st century skills, especially the 4C skills (Critical Thinking, Communication, Collaboration, and Creativity), in the learning process at the secondary school level. Using a qualitative descriptive approach, data were obtained through in-depth interviews with two English teachers at SMPN 27 Makassar. The results showed that teachers had positive perceptions of the application of 21st century skills in teaching English. They considered that 4C skills are very important for forming students who are able to think critically, work together, communicate effectively, and create creative ideas, in line with the demands of a dynamic era. Teachers also recognize their important role in instilling these skills through an active and contextual learning approach. This study reinforces the importance of teachers' understanding of 21st century skills as a foundation for developing relevant and adaptive learning strategies in the modern era.